Cooperative meta-heuristic algorithms for global optimization problems. (15th August 2021) - Abd Elaziz, Mohamed; Ewees, Ahmed A.; Neggaz, Nabil; Ibrahim, Rehab Ali; Al-qaness, Mohammed A.A.; Lu, Songfeng
Highlights: Developed a global optimization approach using cooperative meta-heuristic methods. The proposed method inspired from the natural selection theory. DE, GWO, WOA, SSA, SCA, and SOS are used to build the proposed method. Three variants of proposed are developed based on strategy of updating solutions. Results of proposed method compared with other methods using CEC2014 and CEC2017. Abstract: This paper presents an alternative global optimization meta-heuristics (MHs) approach, inspired by the natural selection theory. The proposed approach depends on the competition among six MHs that allows generating an offspring, which can breed the high characteristics of parents since they are unique and competitive. Therefore, this leads to improve the convergence of the solutions towards an optimal solution and also, to avoid the limitations of other methods that aim to balance between exploitation and exploration. The six algorithms are differential evolution, whale optimization algorithm, grey wolf optimization, symbiotic organisms search algorithm, sine–cosine algorithm, and salp swarm algorithm. According to these algorithms, three variants of the proposed method are developed, in the first variant, one of the six algorithms will be used to update the current individual based on a predefined order and the probability of the fitness function for each individual. Whereas, the second variant updates each individual by permuting the six algorithms, then using the algorithms in the current permutation to update individuals. The third variant is considered as an extension of the second variant, which updates all individuals using only one algorithm from the six algorithms. Three different experiments are carried out using CEC 2014 and CEC 2017 benchmark functions to evaluate the efficiency of the proposed approach. Moreover, the proposed approach is compared with well known MH methods, including the six methods used to build it. Comparison results confirmed the efficiency of the proposed approach compared to other approaches according to different performance measures.